Multi-particulate Systems: Cutting-edge Technology for Controlled Drug Delivery - Wairkar, Sarika; Gaud, Ram; Raghavan, Adhithi (Recent Patents on Drug Delivery & Formulation, 2016)
Background: In the last two decades, multi-particulate dosage forms have caught the attention of formulation scientists due to their tremendous potential as a drug delivery system with a broad range of applications. Methods: Recent patented technologies are focused on designing multi-particulate systems that can enhance therapeutic efficacy and oral bioavailability with minimum systemic toxicity. The technologies offer opportunities to the manufacturers for increasing their market share, especially for competitive generics, and also establishing intellectual property positions. Results: The present paper provides an overview of advanced technologies and patents, based on different principles, for designing multi-particulate dosage forms. The review covers basic characteristics of the current technologies, the mechanisms by which they overcome the limitations of conventional oral dosage forms, and their applications. Conclusion: Comprehensive knowledge of these technologies will expedite further development and platform technologies for multi-particulate controlled drug delivery systems.
Keywords: polymers